Public policy of the state support for the development of bioeconomics and biotechnologies in Ukraine - Нестерова, Катерина Сергіївна; Нестерова, К. С.; Нестерова, Екатерина Сергеевна; Nesterova, Kateryna S.; Яковенко, Алла Олексіївна; Яковенко, А. О.; Яковенко, Алла Алексеевна; Yakovenko, Alla O.; Корощенко, Микола Миколайович; Корощенко, М. М.; Корощенко, Николай Николаевич; Koroshchenko, Mykola M.; et al. (Київ, 2021)
In modern conditions, the climate agenda is one of the key in the international arena, as climate threats are already a «mass weapon» that destroys not only traditional sectors of the national economy, especially agriculture, but also the population, forcing countries to develop and implement policies of the balanced attitude to resources. The key concept in terms of sustainable development is the bioeconomy. The lack of theoretical basis and multi-vector of the bioeconomy, as well as the need for its development in Ukraine in the context of the European integration direction determine the relevance of research in this area. The purpose of the article is to identify current problems facing domestic enterprises in the process of implementing biotechnology, as well as the organizational and economic mechanism of their support in the context of the implementation of state strategic management of bioeconomy in Ukraine. The scientific novelty is to provide recommendations for public management of bioeconomy development in Ukraine, taking into account the progressive world experience. Conclusions. Bioeconomy is the latest concept of the organization of human activity, based on a frugal attitude to resources in order to ensure sustainable development of society. Domestic enterprises face certain problems that limit their ability to implement biotechnologies, the negative impact of which can be minimized through the implementation of effective state regulatory policy. In order to develop the bioeconomy in Ukraine, a comprehensive state policy should be developed on strategic (formulation of strategic guidelines), legal (development of appropriate legal framework taking into account the recommendations of international organizations), instrumental (implementation of a set of economic methods, ways of direct and indirect influence, and also organizational and legal methods). Such a systematic approach to the development of the bioeconomy will contribute to the effective implementation of this concept in Ukraine.

У сучасних умовах кліматична повістка є однією з ключових на міжнародній арені, оскільки кліматичні загрози вже мають характер «масової зброї», яка знищує не лише традиційні галузі національної економіки, передусім сільське господарство, але і населення, що змушує країни до розробки та реалізації політики зваженого відношення до ресурсів. Ключовою концепцією у розрізі забезпечення сталого розвитку є біоекономіка. Недостатність теоретичного підґрунтя та багатовекторність біоекономіки, а також необхідність її розвитку в Україні в контексті євроінтеграційного напрямку обумовлюють актуальність досліджень у цій сфері. Метою статті є визначення сучасних проблем, які стоять перед вітчизняними підприємствами у процесі впровадження біотехнологій, а також організаційно-економічного механізму їх підтримки в контексті реалізації державного стратегічного управління розвитком біоекономіки в Україні. Наукова новизна полягає у наданні рекомендацій щодо державного управління розвитком біоекономіки в Україні з урахуванням прогресивного світового досвіду. Висновки. Біоекономіка – це новітня концепція організації людської діяльності, заснована на ощадливому ставленні до ресурсів з метою забезпечення сталого розвитку суспільства. Вітчизняні підприємства стикаються з певними проблемами, які обмежують можливості впровадження ними біотехнологій, мінімізувати негативний вплив яких можливо шляхом реалізації ефективної державної регуляторної політики. Задля розвитку біоекономіки в Україні має бути розроблена комплексна державна політика на стратегічному (формулювання стратегічних орієнтирів), нормативно-правовому (розробка відповідної нормативно-правової бази з урахуванням рекомендацій міжнародних організацій), інструментальному (реалізація комплексу економічних методів, способів прямого та опосередкованого впливу, а також організаційно-правових методів). Саме такий системний підхід до розвитку біоекономіки сприятиме ефективній реалізації цієї концепції в Україні.
Nesterova K. S. Public policy of the state support for the development of bioeconomics and biotechnologies in Ukraine / K. S. Nesterova, A. O. Yakovenko, M. M. Koroshenko // The Scientific Papers of the Legislation Institute of the Verkhovna Rada of Ukraine: зб. наук. пр. / Ін-т законодавства Верховної Ради України. - № 6. – Київ: [б. в.], 2021. - С. 112-121.
Keywords: bioeconomy; circular economy; biotechnologies; sustainable development; public policy; mechanisms of state regulation; біоекономіка; циркулярна економіка; біотехнології; стійкий розвиток; публічна політика; механізми державного регулювання; Research Subject Categories::SOCIAL SCIENCES::Business and economics